Study of the serum levels of lipocalin-2 as well as of metabolic and oxidative stress markers in alopecia areata patients of the Babil Province - Jawad Al-Daami, Qasim; G. Abdullah, Rawaa; F. Al-Khakani, Manal (Pharmakeftiki, 2025)
Rapid hair loss is caused by the chronic inflammatory disorder alopecia areata, which destroys the hair follicle. Alopecia areata often affects the scalp, although it can also affect other hairy areas such as the beard or the eyebrows. Metabolic abnormalities have been observed in patients with alopecia areata. The aim of this study was to investigate the potential roles of lipocalin-2, insulin, other associated metabolic markers, and oxidative stress in the pathophysiology of alopecia areata. In this case-control study, 90 individuals from the Babil Province of Iraq were recruited: 45 alopecia areata patients and 45 individuals with excellent hair health. Blood samples were collected from them between September 2023 and March 2024, in addition to the medical history and basic clinical measurements of all participants. In our study, alopecia areata patients presented with elevated serum levels of lipocalin-2, insulin, and C-peptide, together with elevated levels of important antioxidant enzymes and oxidative stress markers (as compared to those of age-matched healthy individuals), thereby suggesting a potential disease progression mechanism through metabolic dysregulation.